Effects of brushing with caffeinated toothpaste on neurocognitive function of the central nervous system: a randomized placebo-controlled clinical trial - Zare, Kiarash; Talaei, Mahva; Pahlevani, Amir Hesam; Rezazadeh, Fahimeh; Zare, Kiana; Akbaryari, Masumeh; Naghizadeh, Mohammad Mehdi; Heydari, Mojtaba; Goharinia, Mohsen (Frontiers in Oral Health, 2025)
BackgroundThis randomized placebo-controlled clinical trial aimed to evaluate the effect of brushing with caffeinated toothpaste on neurocognitive function of the central nervous system.MethodsEighty healthy individuals were randomly assigned to four groups: oral caffeine capsules (100 mg caffeine) as the control, brushing with caffeinated toothpaste (100 mg caffeine) for 2, 3, and 4 min. Cognitive and motor responses were assessed using selective processing speed assessment (Stroop test), short-term memory test, selective attention capacity assessment, and hand-eye coordination test before and after intervention at 10, 30, and 60 min intervals.ResultsBrushing with caffeinated toothpaste was as effective as oral caffeine intake in improving selective attention capacity, selective processing speed, short-term memory, and hand-eye coordination. Despite the higher improvement in the longest duration brushing group in most of the outcomes, the difference did not reach the statistical significance among study groups.ConclusionBrushing with caffeinated toothpaste appears to be as effective as oral intake of caffeine in enhance cognitive and motor functions. Clinical Trial Registrationhttps://irct.behdasht.gov.ir/trial/71213, identifier (IRCT20230318057752N2).